Characterization of the vacuum plasma sprayed VPS-Ti/TiC composite coating - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper analyzes the VPS - Ti / TiC composite coating. The powder was deposited at low pressure with an F4 plasma gun produced by Plasma Technik AG because of the influence of the environment on powder oxidation. The main goal of the work was to prevent low-pressure decomposition of TiC cubic carbide into TiO2 and NiTiO3 oxides that reduce: adhesion, cohesive strength, TiC hardness, and abrasion resistance to wear. The mechanical properties and the structure of the Ti / TiC coating were analyzed in accordance with the Pratt & Whitney standard. The microhardness values of the coating layers were in the range of 750-837 HV0.3, and the substrate/coating bond strength was 84 MPa. The coating microstructure was examined by the light microscopy technique. The distribution of TiC in the Ti base is uniform and the deposited layers are obtained without segregation effects. The coating structure consists of titanium layers with β - Ti and α - Ti modifications and TiC cubic layers. In the microstructure, there are unmelted TiC particles present in a smaller share  as well as micropores that did not affect the coating strength. The tests showed that the VPS - Ti / TiC composite coating has good mechanical properties and a good microstructure, which fully enables its application on substrates of biomedical implants.
Keywords: Microstructure; Coatings